Pour une meilleure défensive contre la fraude informatique - Giard, Yves (Assurances)

(untitled) (HEC Montréal, 1984)
It is still difficult to say exactly what measures should be taken to prevent computer theft. Mr. Yves Giard's article indicates that a complete solution is very far away. Much more research on computer information will be needed, and solutions will probably emerge gradually, as we become more familiar with computer operations. For the moment, we can only discuss general ideas, and trust to luck, rather than science, to prevent theft or information leaks, or at least to detect them when they reach a certain scale. Currently, we have the impression of being, if not totally disarmed, at least with very little power of control over the numerous problems that can arise in the field of computer security. The author gives some ideas of accounting practices which are used in certain cases.